State of knowledge for thermohaline conditions on the shelf of West Kamchatka - V. V. Kolomeytsev; S. L. Gorin (Известия ТИНРО)
All available data on water temperature and salinity for the shelf of West Kamchatka are analyzed and all scientific publications and the most important unpublished thesises concerning this area are summarized. Current ideas about the water masses distribution and seasonal and long-term variability of water temperature and salinity on the shelf are discussed. There is noted that the existing estimates of seasonal and long-term variability of water temperature require significant additions for recent times (last 20 years) and certain spatial areas. Insufficient understanding is revealed for spatial-temporal dynamics of salinity in the mixing zone between the river and sea waters that requires special research.